Pengembangan Media Pembelajaran Wordwall Berbasis Web Terhadap Hasil Belajar Siswa Kelas V SD - Maharani, Shella; Erdiana, Lita; Nurhayati, Eni (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2024)
This study aims to determine the feasibility of web-based Wordwall learning media and to improve the learning outcomes of grade V students of IPAS subjects. This research is a type of development research (R&D) using the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. This study collected data through validation of media experts, material experts, lesson plans, pretests, and postests. Validity and effectiveness tests were the data analysis techniques used. The results of media validation reached 92% with very valid criteria, and validation of materials and questions reached 89.5% with very valid criteria. The results of student learning completeness of 93.75% with a very high category show the effectiveness of the media. Students learning outcomes increased significantly before using Wordwall media and after using Wordwall media. The increase resulted in an N-Gain value of 0.7198 with a high category. This shows that Wordwall media is feasible to use as learning media.